Interferon-γ Release Assay for Accurate Detection of Severe Acute Respiratory Syndrome Coronavirus 2 T-Cell Response. (9th October 2020) - Murugesan, Kanagavel; Jagannathan, Prasanna; Pham, Tho D; Pandey, Suchitra; Bonilla, Hector F; Jacobson, Karen; Parsonnet, Julie; Andrews, Jason R; Weiskopf, Daniela; Sette, Alessandro; Pinsky, Benjamin A; Singh, Upinder; et al.
Abstract: We investigated feasibility and accuracy of an interferon-γ release assay (IGRA) for detection of T-cell responses to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Whole blood IGRA accurately distinguished between convalescent and uninfected healthy blood donors with a predominantly CD4 +  T-cell response. SARS-CoV-2 IGRA may serve as a useful diagnostic tool in managing the coronavirus disease 2019 pandemic.